2011
DOI: 10.5402/2011/146915
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism Control in a Child with Cerebral Palsy

Abstract: Cerebral palsy (CP) is one of the most severe childhood disabilities due to a lesion in the developing brain. Oral conditions often observed in this pathogenic are a tendency for the delayed eruption of permanent molars, higher percentages of malocclusion and parafunctional habits, including bruxism. The significance of oral conditions observed in CP patients demonstrates the need for intensive home and professional care for these individuals. This paper presents a 7-year-old boy, with cerebral palsy, severe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The severe wear seen in bruxism with many of these patients is apparent on the lingual cusps of the upper permanent molars and buccal cusps of the lower permanent molars, which leads to loss of vertical dimension and may contribute to problems in the temporomandibular joint. 15,16 However, no bruxism that cause severe wear tooth was diagnosed in the patient described in the present case.…”
Section: Discussionmentioning
confidence: 60%
“…The severe wear seen in bruxism with many of these patients is apparent on the lingual cusps of the upper permanent molars and buccal cusps of the lower permanent molars, which leads to loss of vertical dimension and may contribute to problems in the temporomandibular joint. 15,16 However, no bruxism that cause severe wear tooth was diagnosed in the patient described in the present case.…”
Section: Discussionmentioning
confidence: 60%
“…Stainless steel crowns are one of the best restorative materials in pediatric dentistry. Children with CP have a higher incidence of bruxism and to provide stainless steel crowns in these patients is the best choice to withstand the heavy occlusal load (Oliveira et al, 2011). Complete oral prophylaxis and restorations of all carious teeth should also be done to reduce the colony forming units in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…There is still no proven effective therapy for this parafunction in individuals with CP. Oliveira et al 33 reported the control of bruxism in a child through the use of an acrylic resin protective appliance fixed on both sides of the mandible. Giannasi et al 34 reported the beneficial effect of a hyperboloid chewing appliance for the treatment of severe sleep bruxism in a child.…”
Section: Discussionmentioning
confidence: 99%